2019
DOI: 10.1002/jmr.2805
|View full text |Cite
|
Sign up to set email alerts
|

Role of the non‐hypervariable FR3 D‐E loop in single‐domain antibody recognition of haptens and carbohydrates

Abstract: Single-domain antibodies (sdAbs), the variable domains of camelid heavy chain-only antibodies, are generally thought to poorly recognize nonproteinaceous small molecules and carbohydrates in comparison with conventional antibodies. However, the structures of anti-methotrexate, anti-triclocarban and anti-cortisol sdAbs revealed unexpected contributions of the non-hypervariable "CDR4" loop, formed between β-strands D and E of framework region 3, in binding. Here, we investigated the potential role of CDR4 in sdA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…However, the HV4 region on a heavy chain could be another candidate for such specificity modulation. Some studies called HV4 and LV4 loops “CDR4s” due to their potential effects on antigen binding, 55 our study supports this claim by showing the potential of LV4 for antigen affinity/specificity modulation. Although Vernier zone residues were previously reported to be important for humanization efforts and binding affinity, 33,62 they are mostly underrepresented in the literature 28 .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, the HV4 region on a heavy chain could be another candidate for such specificity modulation. Some studies called HV4 and LV4 loops “CDR4s” due to their potential effects on antigen binding, 55 our study supports this claim by showing the potential of LV4 for antigen affinity/specificity modulation. Although Vernier zone residues were previously reported to be important for humanization efforts and binding affinity, 33,62 they are mostly underrepresented in the literature 28 .…”
Section: Resultssupporting
confidence: 85%
“…These loops reside on Framework‐3 and they are non‐hypervariable 53,54 . Some studies called this loop “CDR4” due to its potential effect on antigen binding 55 . In this study, we show that one of Vernier zone regions, LV4, makes an extraordinary close contact with LCDR1 in dual‐specific antibodies.…”
Section: Resultsmentioning
confidence: 55%
“…In addition, the sensitivity of ic-ELISA based on Nb-3F9 showed the highest sensitivity (Figure 2B), which demonstrated that the sequences in FR could also affect antigen−antibody binding activity although these sequences were universally conserved. 28,29 On the basis of the results above, nanobodies against TeA high sensitivity were isolated by phage display technology along with the stringent biopanning. Moreover, the best anti-TeA clone Nb-3F9 was cloned into the modified pET22b vector containing Nluc gene to generate biofunctional nanobody fusion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Currently, no Nb-based CAR T-cell targeting a TACA has been described. Moreover, obtaining purely anti-glycan Nbs is still challenging 40 . Interestingly, we recently reported the development of a specific Nb against Globo-H, a glycosphingolipid expressed in many solid tumours.…”
Section: Types Of Small Antibody Fragmentsmentioning
confidence: 99%